2011
DOI: 10.1159/000333075
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between Ghrelin Polymorphisms and Alzheimer’s Disease in a Japanese Population

Abstract: Background/Aims: Ghrelin has been reported to enter the hippocampus and to bind to the neurons of the hippocampal formation. This peptide also affects neuronal glucose uptake and decreases tau hyperphosphorylation. There is increasing evidence suggesting an association between ghrelin and Alzheimer’s disease (AD) pathology. The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) of the ghrelin gene are associated with AD. Methods: The SNPs were genotyped using TaqMan technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Several lines of evidence suggest that ghrelin has a critical role in AD pathogenesis and therapy [50,51]. It has been shown that the expression levels of ghrelin and ghrelin receptor were profoundly decreased in the patients with AD [52,53] and the single nucleotide polymorphisms of the ghrelin gene are associated with AD patients [54]. The systemic injection of ghrelin and ghrelin agonist was demonstrated to attenuate the memory impairment in the A␤PP transgenic mouse model of AD [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that ghrelin has a critical role in AD pathogenesis and therapy [50,51]. It has been shown that the expression levels of ghrelin and ghrelin receptor were profoundly decreased in the patients with AD [52,53] and the single nucleotide polymorphisms of the ghrelin gene are associated with AD patients [54]. The systemic injection of ghrelin and ghrelin agonist was demonstrated to attenuate the memory impairment in the A␤PP transgenic mouse model of AD [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that the ratio between GHSR1a and GHSR1b receptors was altered in AD patients, suggesting that these changes in the ghrelin system could be involved in the severity of the disease. The fact that recent data indicate that SNPs of the ghrelin gene are associated with the age of AD onset (Shibata et al 2011), together with the observation that male patients with AD have a disruption in the normal compensatory modulation of ghrelin secretion (Theodoropoulou et al 2012), strongly reinforce the idea that the ghrelin system should be considered as a potential therapeutic target in the treatment of AD-related comorbidities.…”
Section: Neurodegenerationmentioning
confidence: 91%
“…Although there are no reports on genetic association between ghrelin gene polymorphisms and AD [179], it was later reported that ghrelin gene variants are associated with cognitive dysfunction [180]. However, the exact nature of the relationship between ghrelin and cognitive function in healthy subjects is still unclear, since plasma ghrelin levels have been reported to rather be inversely associated with cognitive function in elderly non-demented patients [181].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%